Modification of text encryption based on Elliptic Curve Cryptography (ECC) and Cayley-Purser Algorithm / Nurul Sakinah Ismail - Ismail, Nurul Sakinah (2019)
The modified scheme is considered secure against eavesdroppers if the suitable points on the elliptic curve are remains hard to be found. However, even this problem remains hard today, it is still very likely in the future that efficient algorithms are found and the ECC problem could be solving. Therefore, one of the strategy to surmount this situation is by designing a scheme with multiple hard problems. Motivated from that, this study reviewed the arithmetical properties of elliptic curve and Cayley purser algorithm. After studying the arithmetical properties, this study propose to modify KamalakannanTamilsevans' s scheme (2015) by adding double layers of encryption and decryption. The theoretical aspects of this scheme are analyzed, concluding that the modified scheme have successfully work very well.